The Impact of Violence on Culture in Edward Bond’s Early Morning - Mehtap Demirtürk (Journal of Literature and Humanities)
Edward Bond’s play, Early Morning, serves as a powerful exploration of violence in society by transcending temporal and cultural boundaries. Rooted in the Victorian era, Bond employs historical characters and anachronistic elements to create a narrative that critiques corruption and brutality through a reflection on contemporary societal challenges. The mixture of realism and stylistic experimentation in the play reveals a timeless commentary on morality, corruption, and societal decay. Bond’s masterful blending of historical context with timeless themes invites readers and audiences to draw parallels between the Victorian world presented and the complexities of modern societies. It underscores the role of literature in exposing the darker facets of humanity and serves as a cautionary tale about the enduring nature of human flaws. The universality of violence depicted in the play prompts critical reflections on the human condition. Early Morning investigates the origins of human savagery and gives a striking representation of the aftermath of inappropriate power elements. This article investigates the connection between violence and power as depicted in Bond’s play by working inside the system of Michel Foucault’s arguments on power and its appearances.